SHORTLISTED FOR BEST PAPER AWARD - Andreou, Andreas S. (My University, 2026)
Short-listed for best paper award (with Michalis Pingos, PhD candidate) at the 17th International Conference on Evaluation of Novel Approaches to Software Engineering (ENASE), held in 2022, for our paper entitled “A Data Lake Metadata Enrichment Mechanism via Semantic Blueprints”
Keywords: Sciences